Wawasan Al-Qur'an tentang Sabar - Andi Miswar (Faculty of Adab and Humanities - Alauddin State Islamic University of Makassar, 2010)
Patience is the ability of someone to endure from difficulty of life and to control emotion for the sake ofreaching a target. People are often confronted by collision or condition that bring them into insulation,dissapointment and stress. So that patience can become control of someone personally and socially. Patience does 'not mean surrender bacause it sometime brings someone into fatalism. Patience is a word that covers a whole set of moral values that's most important. In fact, patience is a key for someone to reach success. Qur'an also· suggests human- being to be patient in facing any aspects of life's temptation.